Green-Lipped Mussels (Perna Viridis) as Biomarkers of Petroleum Hydrocarbon Contamination in Selected Coastal Waters of Peninsular Malaysia - Shahbazi, Azadeh (2009)
Over the past few decades, Malaysia is rapidly developing towards being an industrial country. There has been a growing concern in recent years regarding possible harmful effects of industrialization to living aquatic organisms of pollutants released into the marine environment. Polycyclic aromatic hydrocarbons (PAHs) are one of the most important classes of micro-organic pollutants which give rise to this concern. PAHs consist of two or more fused aromatic benzene rings and because of their hydrophobic and persistent nature, they accumulate in tissue of aquatic biota such as mussels. Monitoring of toxic substances in the aquatic environment using green mussels (P. viridis) as a biomonitoring agent is commonly used because of its wide geographical distribution, immobile, easy sampling, tolerance of a wide range of salinity and comparatively long life-span. The present finding focuses on spatial distribution and major sources of petroleum hydrocarbons in green mussels (P. viridis) in Malaysian coastal environment.The results of PAHs monitoring in total soft tissues of P. viridis showed that among the seven stations, mussels collected near Penang Bridge had the highest PAH concentrations (110500 ng/g lipid wt) and Sebatu had the lowest (766 ng/g lipid wt) concentrations of PAHs. The ratios of methyl phenanthrenes to phenanthrene (MP/P ratio) for Penang, Pasir Puteh and Tebing Runtuh (Johore Straits) were greater than 2, indicating extensive input of petrogenic PAHs. The results suggested that male individuals had significant higher concentrations of PAHs in their soft tissues when compared to female individuals. Negative significant correlations (r =−0.890, p<0.01) and (r =−0.0655, p<0.05), were found between weight and total of PAHs in female and male individuals respectively. This indicated that body weight of each individual was not affected by the PAHs concentrations. This study investigates the distribution of trace organic contaminants in tissues (mantle, gills, foot, gonad, muscle, byssus remaining soft tissues), and shell of the P. viridis collected from 8 different geographical locations along the coastal waters of Peninsular Malaysia. The results showed along the eastern part of Johore Straits two stations namely Kg. Pasir Puteh and Senibong recorded the highest bioavailability and contamination by PAHs. Among the different organs studied, gonad was found to be the best organ for biomonitoring of PAHs. The results also indicated significant concentrations of lower molecular weight (LMW) PAHs in different tissues in comparison to higher molecular weight (HMW) of PAHs not only due to greater bioavailability of LMW PAHs but also it could be related to a partial biotransformation of the HMW PAHs rather than to a larger bioavailability of the more water soluble compounds. Molecular indices based on isomeric PAH ratios used to differentiate the pollution sources, and clearly indicate the differences in molecular distribution of PAHs in different soft tissues of P. viridis. Furthermore, the composition and distribution of n-alkanes (C10-C36) and isoprenoid (pristane and phytane) hydrocarbons and hopanes were investigated in different STs and hard tissues of (P. viridis). Total n-alkanes and hopanes concentrations ranged from 154 to 1396597μg/g and 8 to 1681 μg/g dry weights, respectively. The highest levels of alkanes and hopanes were found in gills, and gonads of P. viridis, whereas adductor muscle and shell did not absorb significant amounts of hydrocarbons. The calculated hydrocarbon indexes suggest that petrogenic contamination was the main source of n-alkanes, while both natural and petrogenic sources contributed hopanes to the water column. All the present findings indicated that P. viridis is a good biomonitor of contamination and bioavailability of hydrocarbon pollution in the coastal waters of Peninsular Malaysia.